Studi Sedimentasi di Sungai Batang Lampasi Sedimentation Study at Batang Lampasi River - Dalrino Dalrino; Hartati Hartati; Aguskamar Aguskamar; M. Iqbal Iqbal; Dila Pertiwi (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2019)
BatangLampasi River was located in Talawi village, Nagari Koto Nan GadangPayakumbuh, about 30 km from Bukittinggi, with 48.19 km river length and around 226 km2 Cathment Area. The river flow carries a lot of sediment material, causing siltation on the riverbed which causes the river to overflow in the surrounding area. Sediment transport was triggered by Lampasi watershed erosion, that especially in the upstream section and settling on the riverbed. Prediction of depth decrease caused by sedimentation was conducted. Theoretical flood discharge determined used Nakayasu method. Sediment yield caused by land erosion determined by USLE equation and will compared with total sediment transport that calculated for 5 years return period with Yang's, Engelund Hansen, Ackers and White's methods. HEC-RASS 4.0 was used to find the high of flood water level and also as input hydraulics term to calculating transport sediment. The equivalent value approaching sediment yield was Yang's method where the sediment transport value is 21294,763 tons / year with sediment thickness of 27.24 cm / year. With these deposits thickness we can see from HEC-RASS 4.0 modeling the elevation of high flood water during normal conditions and the presence of thick sediment deposits.